Typodont model study on double keyhole loop in mandibular extraction space closure - CAI Senxin (口腔疾病防治, 2020)
Objective To analyze the impact of the activation mode on the results of space closure in the mandibular arch using a double keyhole loop (DKHL) with a typodont model and reverse engineering technique to provide guidance for clinical treatment. Methods Nine normal mandibular typodont models after leveling were randomly divided into 3 groups, which then underwent three types of DKHL activation for space closure. Each model was assessed at the initial stage and after the warm water bath, and the images were superimposed to measure the displacement of special crown and root mark points. All statistical analysis of the data was performed using SPSS 19.0. Results After equal activation times, the root retraction of anterior teeth and the crown forward position of posterior teeth in groups activated at the distal loop (conditions 2 and 3) were much greater than those in the group activated horizontally (condition 1). Activation between mesial and distal loops (condition 3) induced significant anterior tooth intrusion, together with elongation and buccal inclination of posterior teeth. The displacement of mark points among the three conditions showed a statistically significant difference. Conclusion The movement of mandibular anterior and posterior teeth could be flexibly controlled through different DKHL activation modes, which should be chosen carefully according to individual conditions.